Evaluation of urban air pollution by metal contents of woody vegetation leaves in the urban ecosystem - Zunara Ali; Khawar Sultan; Qamar uz Zaman (International Journal of Applied and Experimental Biology)
Urban air pollution is a major environmental concern, and it should be addressed on a priority basis for human health and the urban ecosystem. The study was performed to investigate and understand the spatial distribution and contamination levels in the leaves of selected plants (Eugenia jambolana, Morus alba, Dalbergia sissoo, Populus deltoides, Ficus religiosa, Ficus variegata, Cassia fistula, Eucalyptus camaldulensis, Melia azedarach, Psidium guajava, Pongamia pinnata, Callistemon citrinus, and Polyalthia longifolia) exposed to the polluted areas of Canal Road, Lahore. Metal concentrations (Pb, As, Cr, and Cd) in the leaves of the plants were analyzed using atomic absorption spectrometry (AAS). The contamination level of As (Average ~1.03 mg/kg) was found to be moderately low in all trees tested except in Eucalyptus camaldulensis (As~2.11 mg/kg). Lead (Pb) accumulation levels in the leaves were observed to be visibly higher in almost all samples (Average ~ 5.34 mg/kg) than the WHO recommended limit (2 mg/kg). Among all samples, Ficus religiosa was found to have the highest levels of Pb. The contamination trends of Cr were observed to be high (Average~1.06 mg/kg) in non-native species, specifically in Eucalyptus camaldulensis (3.21 mg/kg). The Cd concentrations were also found to be higher in all plant samples (Average ~1.90 mg/kg) than the WHO permissible limit (0.02 mg/kg) in plants. Principal Component Analysis (PCA), GIS, and Minitab-19 were also applied to the data. This work is important to set a baseline for future researchers to appraise pollution load in different areas in light of the findings of this study.